THE INSTRUMENTS OF INFORMATION DISPUTE RESOLUTION IN INDONESIA - Imron Rizki Azis; Aidir Amin Daud; Ahmad Muhtaram; Pipit Somefotorono Majid (Jurnal Al-Dustur, 2026)
The term 'public information disclosure' began to receive attention in 2008, following the enactment of the Public Information Disclosure Law, which mandated the establishment of the Information Commission. This institution is expected to guarantee citizens’ rights to access information, including the resolution of information-related disputes. This study investigated the implementation and effectiveness of the existing regulations, with particular emphasis on the role and function of the Information Commission in resolving public information disputes in Indonesia. In addition, the research explored the distribution of judicial authority between the Information Commission and the judiciary. The findings revealed that the existence of the Information Commission has not yet fully ensured effective public information disclosure. Many disputes resolved by the Commission are further escalated to the courts, including to the Supreme Court at the cassation level. This process often causes delays for information requesters and is exacerbated by the non-compliance of certain public bodies with the Commission’s decisions. The study also examined the institutional status of both the Central and Regional Information Commissions. The establishment of regional commissions was found to lack independence, as their formation and status are not structurally integrated with the Central Commission. This research is significant as it centers on the resolution of information disputes and provides a comparative analysis of public information disclosure practices in Indonesia and in other countries such as Sweden, Canada, and Japan.